Cross-sectional association between systemic metal concentrations and immune markers in patients with total joint arthroplasty - Peterson, Stephanie M.; O’Byrne, Thomas J.; Brennan, Peter C.; Jannetto, Paul J.; Pavelko, Kevin D.; Lewallen, David G.; Vassilaki, Maria; Maradit Kremers, Hilal (Frontiers in Immunology, 2023)
Total joint arthroplasty (TJA) implants are composed of metal components. Although they are regarded safe, the long-term immunological effects of chronic exposure to the specific implant materials are unknown. We recruited 115 hip and/or knee TJA patients (mean age 68 years) who provided a blood draw for measurement of chromium, cobalt, titanium concentrations, inflammatory markers and systemic distribution of immune cells. We examined differences between the immune markers and the systemic concentrations of chromium, cobalt and titanium. CD66-b neutrophils, early natural killer cells (NK), and eosinophils were present in higher percentages in patients with chromium and cobalt concentrations greater than the median. The opposite pattern was observed with titanium where the percentages of CD66-b neutrophils, early NK, and eosinophils were higher in patients with undetectable titanium. Cobalt concentrations were positively correlated with a higher percentage of gamma delta T cells. Both chromium and cobalt concentrations were positively correlated with higher percentages of plasmablasts. Titanium concentrations were positively correlated with higher CD4 effector memory T cells, regulatory T cell count and Th1 CD4 helper cells. In this exploratory study, we observed altered distribution of immune cells in TJA patients with elevated systemic metal concentrations. Although these correlations were not strong, these exploratory findings warrant further investigation into the role of increased metals circulating in blood and its role in immune modulation.